2022
DOI: 10.3390/rs14163929
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Wind Field Reconstruction and Validation Using Measurements from SFMR and SMAP Radiometer

Abstract: Accurate information on tropical cyclone position, intensity, and structure is critical for storm surge prediction. Atmospheric reanalysis datasets can provide gridded, full coverage, long-term and multi-parameter atmospheric fields for the research on the impact of tropical cyclones on the upper ocean, which effectively makes up for the uneven temporal and spatial distribution of satellite remote sensing and in situ data. However, the reanalysis data cannot accurately describe characteristic parameters of tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The CWPD 1/3 and SHPD 1/3 are calculated using ERA5 data. Note that previous studies indicated that ERA5 tends to underestimate peak intensity for strong storms (Graham et al 2019, Li et al 2022, and thereby the CWPD 1/3 and SHPD 1/3 are underestimated. The underestimate could influence the trends, while considering that the decreasing trend of CWPD 1/3 is mainly caused by the decline of cold wake size, the influence might not be large.…”
Section: Conclusion and Discussionmentioning
confidence: 86%
“…The CWPD 1/3 and SHPD 1/3 are calculated using ERA5 data. Note that previous studies indicated that ERA5 tends to underestimate peak intensity for strong storms (Graham et al 2019, Li et al 2022, and thereby the CWPD 1/3 and SHPD 1/3 are underestimated. The underestimate could influence the trends, while considering that the decreasing trend of CWPD 1/3 is mainly caused by the decline of cold wake size, the influence might not be large.…”
Section: Conclusion and Discussionmentioning
confidence: 86%
“…The accuracy of these products was systematically investigated. Oceanic modeling primarily relies on atmospheric numerical simulations, and thus, the inherent error for the winds is inevitably included in the modeling techniques, e.g., the under-estimation by ECMWF for TCs [55]. With the abundant remote-sensed data, an interesting question is whether remote-sensed products in near real time could be applied to forecasting and hindcasting, as these do not rely on atmospheric numerical simulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown in the scatter plot in Figure 10, reconstructed high wind speeds (greater than 20 m/s) are significantly underestimated compared to SMAP. We believe this phenomenon is due to the underestimation of strong TC winds in the ECMWF [58,59]. Although the model can reconstruct TC images through learned features, it cannot avoid the limitations of the training set.…”
Section: Reconstruction On Sentinel1-a/bmentioning
confidence: 99%
“…ECMWF is a very commonly used dataset in the wind speed retrieval of remote sensing satellites. However, some studies have shown that ECMWF underestimates high wind speeds [58,59], which may lead to some bias in the features learned by the proposed model. This point is also confirmed by the comparison with SMAP, which indicates that our model tends to underestimate wind speeds in high wind speed ranges.…”
mentioning
confidence: 99%